SLOVAK POETRY IN RUSSIAN INTERPRETATIONS - Natalia Muranska (Polylinguality and Transcultural Practices, 2017)
At the beginning of the 21st century, the two Slovak poetry collections were published in Russian language (“Golosa stoletiy”, 2002 and “Iz veka v vek”, 2006, 2015). The article gives not only the information оn the mentioned two books, but much attention is given to the way of translation of Slovak authors (M. Valek, L. Feldek, S. Strazhay) by Russian translators (B. Okudzhava, O. Malevich,Mashkova, N. Shvedova). It is shown that the Russian translators retain their own perception, feeling and understanding of Slovak poetry. Certain inadequate transformations in the translation are noticeably just in the stylistic and semantic levels, as well as in the not a full understanding of some specific Slovak historic-cultural reality by translators.